CONTINGENCY PLANS DAN RELEVANSINYA DENGAN ERA DISRUPSI PADA LEMBAGA PENDIDIKAN - Imron; Sirozi, Muhammad (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Education has a very important role in maintaining the value of the nation and giving birth to quality individuals who are competitive in various fields. Educational institutions as institutions that organize the educational process need to be able to adapt to the times, especially in facing the challenges of the digital era which is full of disruption. Disruption in education is related to rapid technological changes, increasingly diverse ways of learning, and increasingly open access to information. This phenomenon requires educational institutions to adjust to remain relevant. One strategy that can be applied to deal with the era of disruption is contingency planning. These plans facilitate the rapid adaptation of educational institutions and the mitigation of the impact of disruptions. This research project aims to explore the relevance of contingency planning in the context of educational institutions in the era of disruption. Adopting a descriptive qualitative approach, the research identifies the importance of contingency planning as a strategic tool for educational institutions to survive and operate amidst uncertainty. Contingency plans are considered the optimal solution for dealing with technological disruption, social change, and unexpected events. With a robust contingency plan in place, educational institutions can be better prepared to deal with disruptions and changes that occur more flexibly and effectively.